Desenvolvimento de modelos hardware-in-the-loop para avaliação e testes de firmware para motores síncronos de imãs permanentes aplicados em sistemas de refrigeração - Moura, Emmanuel Adamski de (2024)
This master thesis presents an evaluation of the Hardware-in-the-Loop (HIL) simulation tool for accelerating the development and validation process of control firmware for electric motors applied to volumetric compressors in residential refrigeration systems. With the increasing demand for energy efficiency, speed-controlled refrigeration systems are gaining market prominence. These systems enable control over the cooling rate and are compact due to the use of Permanent Magnet Synchronous Motors (PMSMs), which have high power density. Therefore, the development of control firmware becomes a fundamental project stage, significantly increasing application complexity. Thus, this work presents a study of the HIL simulation tool aimed at accelerating product development in an industrial environment. The aspects of modeling PMSMs and compressors in an HIL environment are addressed. Two PMSMs are studied, one with surface mounted permanent magnets and the other with interior permanent magnets, both present in market-available volumetric compressor models. The electrical and mechanical parameters of these machines, as well as experimental data on the thermodynamic behavior of these compressors, were provided by the manufacturer for this research. The evaluated machines are applied in different products, having different drive systems. Therefore, this dissertation aims to model in HIL and validate the drives of both. HIL simulation results considering the dynamic model of the compressor are presented. Finally, strategies for implementing automatic test routines replicable in an industrial environment are discussed, in order to accelerate the development and validation process of control firmware.